The Effect Of Facial Exercise On The Amount Of Salivary Secretion In The Elderly At The Mandiangin Health Center Bukittinggi City - Ningrum, Valendriyani; Ghaniyyu, Ghaniyyu; Orienty, Fauzia Nilam (Odonto : Dental Journal, 2025)
Background: Elderly  is one of the phases in human life. There are several changes in body and organ function, one of which is a decrease in oral cavity function such as decreased saliva production. Decreased salivary secretion will cause poor oral conditions. One way to prevent this is by doing facial exercises. Facial exercises can stimulate salivary secretion and oral functionMethod: Quasi experimental research method with one group pre test post test design. The sampling technique used Purposive sampling with a total sample of 78 samples where the subject spat saliva 2 times before facial exercise, then performed facial exercise, the subject fasted for one hour and the subject was asked to spit saliva again 2 times.Result: The results of this study were analyzed using the Wilcoxon Signed Ranks test. The gender of the respondents was mostly female as many as 68 people (86.1%), while male respondents were 11 people (13.9%), the average age of respondents in this study was 65 years old with the most respondents aged 68 years, the average salivary secretion before facial exercise 1.11 ml and the average after facial exercise 1.62 ml the results of statistical analysis of significance p value 0.001 (p < 0.05) showed a significant difference between the amount of salivary secretion before and after doing facial exercise.Conclusion: The   conclusion  of   this   study  is   that   facial  exercise  has an  effect on  increasing the  amount of salivary secretion in elderly.